A CAD–CAM-prototyped temporomandibular condyle connected to a bony plate to support a free fibula flap in patients undergoing mandiblectomy: A pilot study with 5 years of follow up. Issue 7 (July 2016) - Ciocca, Leonardo; Tarsitano, Achille; Marchetti, Claudio; Scotti, Roberto
Abstract: Reconstruction of the condyle after an ablative procedure with the aim of cancer elimination remains surgically challenging. This pilot study focused on mandibular condylar replacement using CAD–CAM temporomandibular prostheses connected to customized reconstructive plates to support free fibula flaps in oncological patients. Five patients underwent mandibular disarticulation resection, and two of them completed their 5-year follow ups. The condylar anatomy, the position of the condyle within the glenoid fossa, and glenoid anatomy were measured by superimposing pre- and postoperative CT images (obtained after 6 months and 5 years of follow up). When comparing condyle anatomy, the shift was no more than 0.19 mm; when calculating condyle downward displacement the values were inferior to 2.92 mm; when analyzing glenoid fossa thickness, in case #1, glenoid fossa thickness increased by 0.62 and 0.48 mm at the 6-month and 5-year follow ups, respectively, and in case #2 were 0.50 and −0.11 mm, respectively. The hypothesis that the absence of anatomical change would prevent biodynamic alteration of tissues of the articulation chamber (the glenoid fossa, the synovial liquid, and the disc) was confirmed by the preliminary findings of this study.